2020
DOI: 10.1590/1984-3143-ar2020-0057
|View full text |Cite|
|
Sign up to set email alerts
|

New approaches to diagnose and target reproductive failure in cattle

Abstract: Reproductive failure and pregnancy loss in cattle are some of the largest economic burdens to cattle producers and one of most perplexing factors influencing management decisions. Pregnancy loss may occur at any point during gestation with the largest percentage of loss occurring in the first 30 days and, subsequently, decreasing as the pregnancy progresses. Losses may be attributed to numerous factors, predisposed issues or environmental conditions such as nutritional stressors or disease. From a research per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 124 publications
(192 reference statements)
2
21
0
17
Order By: Relevance
“…The disadvantage of this method is that before 28 days of gestation it is not predictive of embryonic mortality. This is in agreement with what has been reported by other authors of bovine pregnancy studies [16,60,68].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The disadvantage of this method is that before 28 days of gestation it is not predictive of embryonic mortality. This is in agreement with what has been reported by other authors of bovine pregnancy studies [16,60,68].…”
Section: Discussionsupporting
confidence: 94%
“…Uterine environment is critical as the embryo transcends from the oviduct to the site of implantation. Asynchrony between the uterus and the embryo can be problematic as the uterine environment will not wait for an embryo, although an embryo can accelerate or decelerate its development to some degree [ 60 , 61 ]. At day 40, all the animals in which there was a recognized embryonic vesicle and the embryo proper with heartbeat maintained pregnancy until the end of the observation period (60 days post-AI), while no buffaloes in the mortality group showed vesicle + embryo + heartbeat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Pohler et al [14] have suggested using the terms 'early embryonic development' until Day 30 and 'late embryonic development' between Days 31 and 45 of gestation. Due to the fact that different technical terms are used for this period, perhaps it would be easier to divide the former late embryonic period between Days 16 to 42 into two stages, namely, stage 1 between Days 16 and 30 and stage 2 between Days 31 and 42/45 of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive efficiency is vital to cow-calf producers to reduce losses and maintain profit. Infertility, defined as the inability to develop and maintain a pregnancy in a defined breeding season, is estimated to cost the beef and dairy industries over $1 billion annually in the United States (Bellows et al, 2002;Pohler et al, 2020). Infertility can be attributed to numerous factors such as genetics, nutrition, body condition, environmental stress, or disease.…”
Section: Introductionmentioning
confidence: 99%